TECHNICAL MEANS OF CONTROL AND MANAGEMENT OF NATURAL RESOURCES MONITORING OF RUSSIAN SOUTH REGION - Y.A. BATISHEV (Вестник Донского государственного технического университета, 2018)
The article is devoted to most important questions of rational nature using, environment protection and population health. There are formulated principals of monitorring system. The article describes the complex of technical means for comprehensive checking of earth condition and low altitude atmosphere. There are pointed at way to show output data and domain of it potential using. The conclusion of article describe the next steps improvement of system, adaptation system to region needs and perspectives of it development.